Poligami Perspektif Ulama Banjar - Abdul Helim (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2017)
This article attempts to discuss the views of Banjarese â€˜ulama and the legal method used in responding to the issue of polygamy. The Banjarese ulama interviewed are nine. This study reveals the existence of different opinions among the Banjarese ulama. There are many ulama who accept polygamy, the minority being not too rigid in terms of conditions for polygamy, while the majority emphasize rigid conditions. However, there are ulama who reject polygamy due to various considerations and recent conditions. The desire to polygamy can be tolerated, but the conditions are required. The difference of opinions between the Banjarese ulama cannot be separated from the method of Islamic law used in understanding this phenomenon. If related to uá¹£Å«l al-fiqh, most views of the Banjarese ulama with regard to polygamy can be concludedas using the method of istiá¸¥sÄn and dharÄ«â€˜ah.